Investigating the Relationship between Stress Management and the Quality of Working life of Nurses in Teaching Hospitals in Yazd in 2023 - Hasan Jafari; Mohammad Kazem Rahimi; Farnoosh Ghomi; Mahdieh Yavari (تحقیقات سلامت در جامعه, 2024)
Introduction and purpose: Considering the impact of work stress on nurses' quality of life, stress management is of great importance. Therefore, the present study investigated the relationship between these two factors in the teaching hospitals of Shahid Sadougi University of Medical Sciences in Yazd in 2023. Methods: In this descriptive cross-sectional study, the statistical population comprised working nurses, 123 of whom were selected using proportional stratified random sampling. 1981), frequency, mean and standard deviation as well as Pearson correlation test, t-test and ANOVA were used for data analysis with SPSS version 26 software. Results: Among the dimensions of job strain, nurses had the highest stress (8.38 ± 4.97) and the lowest (2.31 ± 2.09) in the dimension of suffering and death of patients. In the dimensions of quality of work life, the highest mean score was in desire and motivation to work (15.28 ± 2.21) and the lowest in problem solving (8.65 ± 2.54). According to the results of the present study, there is a statistically significant relationship between occupational stress and the quality of nurses' work life (P-value<0.001 and rs=0.399). Conclusion: Considering the impact of stress on the quality of work life of nurses, managers and responsible officials should take measures to reduce stress. In addition, the existing knowledge can serve as evidence for the relevant managers and officials so that they can take action to eliminate the influential problems with the knowledge of the current situation.